2010
DOI: 10.1074/jbc.m109.059741
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Down-regulation of Adenylyl Cyclase Isoforms and the Stimulatory G Protein (Gs) in Intestinal Epithelial Cell Differentiation

Abstract: The intestinal epithelium is dynamic, with proliferation of undifferentiated crypt cells balanced by terminal differentiation and cell death at the colon surface or small intestinal villus tips. Cyclic AMP, induced by agonists such as prostaglandin E 2 and vasoactive intestinal polypeptide, promotes proliferation and ion secretion and suppresses apoptosis in intestinal epithelial cells. Here, we show that cell differentiation in a model intestinal epithelium leads to attenuation of cAMP production in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…In the present study, the HFD-induced decrease in total Adcy activity observed in visceral adipose tissue of both WT and Adcy3 +/ − mice was accompanied by downregulation of Adcy1 , Adcy2 , Adcy3 , and Adcy8 mRNA expression. This finding is in line with previous reports indicating that expression of Adcy isoforms in a specific cell or tissue type can be selectively changed in response to pathophysiologic stimuli 25 26 . Choi et al observed that treatment of human colon epithelial cells with butyrate, which induced cell differentiation, downregulated mRNA expression of Adcy3 , Adcy4 , Adcy6, and Adcy7 by 70–90%, while mRNA levels of the other three isoforms, including Adcy1 , Adcy5 , and Adcy9 , were unchanged 25 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the HFD-induced decrease in total Adcy activity observed in visceral adipose tissue of both WT and Adcy3 +/ − mice was accompanied by downregulation of Adcy1 , Adcy2 , Adcy3 , and Adcy8 mRNA expression. This finding is in line with previous reports indicating that expression of Adcy isoforms in a specific cell or tissue type can be selectively changed in response to pathophysiologic stimuli 25 26 . Choi et al observed that treatment of human colon epithelial cells with butyrate, which induced cell differentiation, downregulated mRNA expression of Adcy3 , Adcy4 , Adcy6, and Adcy7 by 70–90%, while mRNA levels of the other three isoforms, including Adcy1 , Adcy5 , and Adcy9 , were unchanged 25 .…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with previous reports indicating that expression of Adcy isoforms in a specific cell or tissue type can be selectively changed in response to pathophysiologic stimuli 25 26 . Choi et al observed that treatment of human colon epithelial cells with butyrate, which induced cell differentiation, downregulated mRNA expression of Adcy3 , Adcy4 , Adcy6, and Adcy7 by 70–90%, while mRNA levels of the other three isoforms, including Adcy1 , Adcy5 , and Adcy9 , were unchanged 25 . Furthermore, Suzuki et al reported that among four isoforms of Adcys (Adcy2 , Adcy6 , Adcy7 , and Adcy 9) detected in the gastrocnemius muscle, Adcy 2 and Adcy 9 mRNA were selectively downregulated after denervation carried out by excision of the left sciatic nerve at the midthigh region 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the combined effect of Li + and AC6 deletion could have a positively additive effect on the IC-to-PC ratio. Whether AC6 in the kidney is an indicator/modulator of differentiation as described in the mouse colon (44), in which AC6 is downregulated in the most differentiated surface cells, remains to be determined. However, based on the current data, it is plausible that AC6 plays distinctive roles in epithelial cell proliferation and may even be a determinant of the conversion of PC to IC (45).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PR2/4 increase cAMP production which promotes cell growth and inhibits apoptosis . Downregulation of adenylyl cyclase isoforms and G α s, is an integral part of the intestinal epithelial differentiation program, perhaps serving to release cells from a cAMP‐promoted antiapoptotic state that could be a prerequisite for cell death upon terminal differentiation.…”
Section: Functional Outcomes Of Cyclic Nucleotide Signaling In Epithementioning
confidence: 99%